2001
DOI: 10.1128/mcb.21.14.4647-4655.2001
|View full text |Cite
|
Sign up to set email alerts
|

Bmx Tyrosine Kinase Has a Redundant Function Downstream of Angiopoietin and Vascular Endothelial Growth Factor Receptors in Arterial Endothelium

Abstract: The Bmx gene, a member of the Tec tyrosine kinase gene family, is known to be expressed in subsets of hematopoietic and endothelial cells. In this study, mice were generated in which the first coding exon of the Bmx gene was replaced with the lacZ reporter gene by a knock-in strategy. The homozygous mice lacking Bmx activity were fertile and had a normal life span without an obvious phenotype. Staining of their tissues using ␤-galactosidase substrate to assess the sites of Bmx expression revealed strong signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 40 publications
4
76
0
Order By: Relevance
“…Together with the data of Flk-1/ KDR/VEGFR-2 being present in TR-BBB cells and HUVEC (this report and Zeng et al, 2001), it is conceivable to conclude that Etk induces VEGF expression and that subsequently the secreted VEGF binds to Flk-1/KDR/VEGFR-2 to modulate endothelial cellular processes in an autocrine manner. Studies with Etk/Bmx knockout mice demonstrated that Etk/ Bmx-null mice are viable and without an obvious phenotype, at least in the context of DBA/2 background (Rajantie et al, 2001). Although this observation suggests that Etk-mediated signaling may be a redundant pathway, it does not rule out the possibility that enhanced Etk-dependent signaling exerts a positive modulatory effect on various cell behaviors, rendering adaptive responses to noxious environment.…”
Section: Discussionmentioning
confidence: 76%
“…Together with the data of Flk-1/ KDR/VEGFR-2 being present in TR-BBB cells and HUVEC (this report and Zeng et al, 2001), it is conceivable to conclude that Etk induces VEGF expression and that subsequently the secreted VEGF binds to Flk-1/KDR/VEGFR-2 to modulate endothelial cellular processes in an autocrine manner. Studies with Etk/Bmx knockout mice demonstrated that Etk/ Bmx-null mice are viable and without an obvious phenotype, at least in the context of DBA/2 background (Rajantie et al, 2001). Although this observation suggests that Etk-mediated signaling may be a redundant pathway, it does not rule out the possibility that enhanced Etk-dependent signaling exerts a positive modulatory effect on various cell behaviors, rendering adaptive responses to noxious environment.…”
Section: Discussionmentioning
confidence: 76%
“…In light of this, it is possible that the vascular abnormality observed in these mice might reflect an up-regulation of the kinase activity of Bmx, an endothelial and epithelial specific tyrosine kinase that has been shown to be involved in various signaling events of angiogenesis and vascular disease (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we isolated Etk-null EC from Etk-null mice (35) to determine the role of Etk in TNF signaling. Mouse lung EC (MLEC) from Etk-null mice were isolated as described previously (23).…”
Section: Etk Specifically Mediates Tnf (But Not Vegf)-induced Activatmentioning
confidence: 99%